Temperaturentwicklungen in der Beaufort See: Implikationen für Methanemissionen aus dem Meeresboden - Kretschmer, Kerstin (2010)
The effects of global warming on the stability of gas hydrates are investigated in the shelf regions of the Beaufort Sea. The mean conditions as well as the natural occuring variability of the bottom water temperatures in terms of the anthropogenic influences are examined. The analysis of the structure and variability of the bottom water temperature over the period from 1958 to 2004 was performed with the global ocean/sea-ice configuration ORCA05. The future climate trend was simulated with the Kiel Climate Model. An ensemble of eight 100-year long climate scenarios was available. The gas hydrate stability analyses are based on the calculations of the dissociation pressure. The gas hydrate stability mainly depends on pressure and temperature conditions in the water column. Therefore the temperature changes in the shelf regions of the Beaufort Sea had come into focus. The analysis of the bottom water temperatures resulted in a warming of the shelf of about 1.5 ◦C within the next 100 years. This can be ascribed to the influence of the Atlantic inflow. Due to the increasing warming in the boundary layers of the Beaufort Sea the possibly stored methane hydrate could be destabilised. As a consequence, methane gas could be released into the water column. This could lead to an interaction with the atmosphere and hence accelerate the natural greenhouse effect. A significant impact of the Atlantic inflow on the gas hydrate stability zone was verified. Especially in the shelf regions a phase shift from hydrate to gas can occur resulting in a possible gas release into the atmosphere. This would enhance global climate change.